Obstetric and perinatal outcomes in parturients with active SARS-CoV-2 infection during labor and delivery: a retrospective cohort study - Rita Zlatkin; Sarah Dollinger; Chen Jacoby; Anat Shmueli; Shiri Barbash-Hazan; Rony Chen; Arnon Wiznitzer; Eran Hadar (BMC, 2022)
Abstract Background The COVID-19 pandemic is an ongoing global healthcare crisis that negatively affects pregnant women. Although patients with an acute infection during pregnancy have been widely studied, information regarding labor and delivery while infected is sparse. The aim of the study was to ascertain maternal, obstetrical, and perinatal outcomes of women who gave birth while infected with SARS-CoV-2. Methods Patients diagnosed with COVID-19 during pregnancy at a tertiary medical center in 4/20-2/21 were identified by a retrospective database search. Those with an active intrapartum SARS-CoV-2 infection were compared with those who recovered at least 10 days before labor and delivery. Results Of the 176 women included in the study, 84 had a SARS-CoV-2 infection at the time of delivery and 92 had recovered from the infection. There was no statistically significant between-group difference in mean gestational age at delivery (39 weeks for both, p = 0.71) and overall rate of cesarean delivery (26.2% vs 17.4%, respectively, p = 0.35) or non-elective cesarean delivery (10.71% vs 4.34%, respectively, p = 0.48). In the active-infection group, the rate of severe disease was 2.4%, and of critical disease (with intensive care unit admission, mechanical ventilation, and ECMO), 3.6%, compared to zero for both in the recovered group. No differences were found between the groups in adverse perinatal outcomes. Conclusion Delivery is safe and feasible in women with active SARS-CoV-2 infection. Nevertheless, we found a non-significant trend for more severe disease and for cesarean delivery and urgent cesarean delivery (for COVID-19-related indications) in women with an intrapartum SARS-CoV-2 infection.